Original paper>Coronary artery bypass grafts angioplasty conducted by 64-slice spiral computed tomography - Ochała, Andrzej; Syzdół, Marcin; Wieja, Paweł; Garbocz, Piotr; Sosnowski, Maciej; Cybulski, Wiesław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background : Multislice spiral computed tomography (MSCT) is an alternative diagnostic method for coronary artery bypasses (CABG) that could enable us to perform graft percutaneous coronary intervention (PCI) almost without angiography. Aim : The aim was to investigate the efficiency of MSCT in testing the permeability of coronary artery bypasses and possible constriction in the group of symptomatic patients in class CCS II or greater. The other aim of this study was to compare the non-invasive method (MSCT) with the invasive one (angiography) and to determine its sensitivity, specificity and diagnostic accuracy. Material and methods : Fifty-eight symptomatic patients after CABG were involved in the study. We analysed 128 bypass grafts (32 arterial and 96 vein). In this group in 17 patients (43.5% of cases) we had to perform PCI of the graft or the native coronary artery. Results: Nine occluded and 2 constricted arterial coronary bypasses were found and 16 occluded, 6 constricted vein coronary bypasses in MSCT. In conventional coronarography used as the reference method 7 occluded, 2 constricted arterial coronary bypasses and 17 occluded, 5 constricted vein coronary bypasses were confirmed. The sensitivity and specificity of MSCT were very high. The time of the procedure, amount of contrast and dose of radiation were significantly higher during PCI based on the traditional bypass angiography. Conclusions : The PCI of grafts based only on 64-slice MSCT is safe and the sensitivity, specificity and accuracy of this diagnostic method are very high. The procedure based on non-invasive qualification significantly decreased the amount of contrast and fluoroscopy.